The effect of mobile applications used during pregnancy on prenatal distress and attachment - Nurdilan, Sener Cetin; Simge, Ozturk (Bmc, 2026)
Background Prenatal distress during pregnancy may increase pregnancy complications and negatively affect mother-fetus bonding. Today, mobile health applications play an important role in pregnant women's search for information and support. This study aims to examine the effects of mobile applications used during pregnancy on prenatal distress level and prenatal attachment. Methods This descriptive and comparative study was conducted between March and June 2025 in an obstetrics outpatient clinic of a university hospital in eastern Turkey. The study included 313 pregnant women who were at or after the 32nd week of pregnancy, graduated from at least primary school, used smartphones, did not have risky or multiple pregnancies, and did not have any diagnosed psychiatric illness. Data were collected by face-to-face interviews using the Personal Information Form, Prenatal Attachment Scale (PAS) and Prenatal Distress Scale (PDS) developed by the researcher. Results 35.1% of the participants stated that they used pregnancy-related mobile applications. The most preferred application was Happy Mom with 42.7% and 80% of the applications had the feature of sending notifications. The mean scores of the total score and sub-dimension scores of the PAS were found to be statistically significantly higher and the mean scores of the total score and sub-dimension scores of the PAS were found to be significantly lower in pregnant women using mobile applications (p < .05). Conclusion The study shows that the use of mobile applications during pregnancy is associated with higher prenatal attachment levels and lower prenatal distress levels. Mobile applications may support women in adapting to the pregnancy process and in strengthening the mother-fetus bond, although causality cannot be firmly established due to the cross-sectional design of the study.
Keywords: Pregnancy; Mobile application; Prenatal distress; Prenatal attachment; Digital health